Telecommunications regulation, mobile money innovations and financial inclusion - Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
This study assesses how corporate telecommunication (telecom) policies follow telecom sector regulation in mobile money innovation for financial inclusion in developing countries. Telecom policies are understood in terms of mobile subscriptions, mobile connectivity coverage and mobile connectivity performance while mobile money innovations represent mobile money accounts, the mobile used to send money and the mobile used to receive money. The empirical evidence is based on Tobit regressions. Telecom sector regulation positively influences mobile money innovations. From net influences, mobile subscriptions and connectivity policies moderate telecom sector regulation to positively influence mobile money innovations; exclusively within the remit of mobile money accounts because the corresponding net influences on the mobile used to send money and the mobile used to receive money are negative. The interactive influences are consistently negative and hence, thresholds for complementary policies are provided in order to maintain the positive influence of telecom sector regulation on mobile money innovations. This study has complemented the extant literature by assessing how corporate telecommunication policies follow telecommunication sector regulation in mobile money innovations for financial inclusion.
Keywords: D10; D14; D31; D60; O30; 330; Mobile money; technology diffusion; financial inclusion; inclusive innovation